0498 Biomarkers of concussion. (21st August 2017) - Gall, Valentina; McElvenny, Damien; Pearce, Neil
Abstract : Concussion is a frequent occurrence in many contact sports and among soldiers, but also a possible inevitably consequence of accidents. Currently, the diagnosis of concussion is based on clinical symptoms, and it is difficult to predict prognosis. Biomarkers could be of invaluable help in informing the neuropathological events underlying concussive episodes. Specifically, they could contribute defining the diagnosis, the recovery process, and the long-term effect in presence or absence of chronic traumatic encephalopathy. For diagnosis and recovery, the neurofilaments and tau protein are promising biomarkers. No markers for CTE have been developed to date. The identification of biomarkers of diagnosis and recovery is particular important as most current research suggests that the risk of long-term symptoms following concussion is highest in individuals who have received repetitive concussions before the brain has recovered properly.